Association of miR-146a gene polymorphism and expression levels of its target protein RhoA in Pakistani Breast Cancer Patients - Amena Rahim; Muhammad Afzal; Abdul Khaliq Naveed; Muhammad Naeem (Journal of the Pakistan Medical Association, 2020)
Objective: To assess the association of miR-146a and its target protein RhoA expression levels in breast cancer. Methods: The case-control study was conducted at Riphah International University, Islamabad, Pakistan, from March 2017 to November 2018, and comprised confirmed breast cancer cases and controls who were matched for age and ethnicity. Genotyping and expression profiling of archived samples was performed. Data was analysed using SPSS 22.. Results: Of the 590 subjects, 295(50%) each were cases and controls. Among the cases, there were 195(66%) Punjabis, 59(20%) Pathans and 41(14%) Kashmiris. The corresponding numbers among the controls were 198(67%), 58(19.7%) and 39(13.2%). The association between genotypes of the cases and controls was significant (p<0.05). Strong association was seen in dominant, recessive and allelic models (p=0.05). In Punjabi group the association was (p<0.00) significant, but this association was not significant in Kashmiri and Pathan groups (p>0.05). No association was found with the receptor status and miR-146a polymorphism. Conclusion: The miR-146a gene polymorphism rs2910164 G/C was found to have increased susceptibility to breast cancer at genotype and allelic levels. Key Words: Single nucleotide polymorphism, Breast cancer, miR-146a, RhoA. Continuous..